Insight into the stereoselectivity of TS-1 in epoxidation of cis/trans-2-hexene: a computational study. Issue 19 (5th September 2018) - Li, Mengzhao; Yan, Xiaoyue; Zhu, Meiyu; Wang, Meiqi; Zhou, Danhong
Abstract : The mechanism of the stereoselectivity for cis / trans -2-hexene epoxidation in TS-1 zeolite was studied using density functional theory and the ONIOM scheme. Abstract : The mechanism of the stereoselectivity for cis / trans -2-hexene epoxidation in TS-1 zeolite with hydrogen peroxide has been investigated using density functional theory with the ONIOM scheme. A cluster model of 136T with Ti(iv ) at the T8 site of TS-1 was adopted to mimic the zeolite catalyst. Four different Ti-hydroperoxo intermediates were constructed and optimized. The stability order is Ti-η 2 (OOH)–H2 O–(Hβ )H2 O > Ti-η 2 (OOH)–H2 O > Ti-η 2 (OOH)–(Hβ )H2 O > Ti-η 2 (OOH). The activation energies of cis -2-hexene epoxidation over Ti-η 2 (OOH), Ti-η 2 (OOH)–H2 O, Ti-η 2 (OOH)–(Hβ )H2 O, and Ti-η 2 (OOH)–H2 O–(Hβ )H2 O active centers are 38.6, 53.6, 52.1, and 64.0 kJ mol −1, respectively. The corresponding activation energies for trans -2-hexene epoxidation are 60.1, 55.2, 80.5, and 85.8 kJ mol −1, respectively. cis -2-Hexene had a lower activation energy barrier than trans -2-hexene. The Ti-η 2 (OOH)–H2 O species is likely the real active center; the ratio of the rate constant of the cis -2-hexene to trans -2-hexene epoxidation is 1.7, which agrees nicely with the experimental results. The decisive factor for cis -selectivity depends on the microstructure of the Ti-hydroperoxo intermediate and the confinement effect in TS-1 zeolite. At the transition state, cis -2-hexene is forced to adopt a twisting conformation and embeds suitably in the zeolite cavity under the action of confinement. This leads to increased stability and reduced activation barriers.